Preparation and Characterization of Some New Azoxine S Azo Dyes - El-Ansary, A.L.; El-Hawary, W.F.; Issa, Y.M.; Ahmed, A.F. (Asian Journal of Chemistry, 2010)
New azoxine S dyes were prepared by coupling some diazotized sulpha drugs with 8-hydroxyquinoline-5-sulphonic acid. Their structures were investigated using elemental analysis, IR and NMR absorption spectra and thermogravimetric analysis. The UV and visible absorption spectra of the prepared compounds were scanned in ethanol and the absorption bands were assigned to their electronic transitions. The UV and visible spectra were scanned also in different solvents of varying polarities and the relations between different solvent parameters and λmax were plotted, but no linear relations were obtained; so there is no single parameter that affects spectral shifts. The ionization constants of the ionizable groups of the prepared azoxine S dyes were calculated spectrophotometrically using the half height and limiting absorbance methods.